Penerapan Metode Queue Tree Pada Bandwidth Management Mikrotik (Studi kasus : SMK Swadhipa 1 Natar) - Endri Paryanto; Dodi Afriansyah; Doni Eko Hendro P (Jurnal Teknologi dan Informatika (JEDA), 2022)
The purpose of this study is to apply bandwidth management with the PCQ - Queue Tree method so that bandwidth usage in one network can be comprehensive/normal and share good Quality Of Service in one network. The background of this research is that the internet network is less than optimal due to some triggers. Both in terms of infrastructure or systems. By applying the Peer Connection Queue (PCQ) method using a Queue Tree, every user who accesses the internet will get an even bandwidth allocation. The test uses the Wireshark application with several computers connected via wired and several devices connected via a wireless network. The results showed that bandwidth management with the PCQ - Queue Tree method gave better results than without using PCQ because by using PCQ all users who are members of one network get an equal bandwidth allocation between one another.